The Performance of Socially Responsible Investments in Indonesia: A Study of the Sri Kehati Index (SKI) - Abdul Hadi Zulkafli; Zamri Ahmad; Eky Ermal M (Gadjah Mada International Journal of Business, 2017)
This study examines the performance of the Sri Kehati Index (SKI) against the Jakarta Composite Index (JCI) as the market index, using respective daily index prices from the 1st of January 2009 to the 31st of December 2014. This study uses the risk-adjusted return of Sharpe’s Index, the Adjusted Sharpe’s Index (ASI), Treynor’s Index, Jensen’s Alpha Index, the Adjusted Jensen’s Alpha Index (AJI) and Sortino’s Ratio to examine the performance of the SKI and the JCI. Except for Sharpe’s Index and the Adjusted Sharpe’s Index, the risk-adjusted return performance of the SKI, (Treynor, Jensen’s Alpha, Adjusted Jensen’s Alpha and Sortino) outperforms the JCI as the conventional benchmark. However, Jensen’s Alpha is the only performance measure that is significant and therefore supports that the SKI outperforms the JCI during the overall period from 2009 to 2014. As there is a contradiction between the adjusted returns of Sharpe’s Index/Adjusted Sharpe’s Index and Jensen’s Alpha Index, the hypothesis that the SKI presents a higher risk adjusted performance than the JCI does cannot be accepted. Even though the performance of SKI in this study is slightly lower over the whole period of the study, it is still generating competitive returns.